1978
DOI: 10.1172/jci109189
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus antibody interaction with human epidermal cells in culture.

Abstract: A B S T R A C T The mechanism of pemphigus acantholysis has been studied with an in vitro system. Freshly prepared human skin epidermal cells were incubated in F-10 medium which contained the immunoglobulin G fraction from either pemphigus serum or normal human serum. During 18-h incubation periods, the pemphigus antibody became bound to the surface ofthe epidermal cells, caused the destruction of 75% of the viable cells as compared to only 14% in the normal immunoglobulin G controls (trypan blue exclusion), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…Exactly how autoantibodies from these patients interact with these molecular complexes to cause loss of cell adhesion, whether directly by interfering with their function or indirectly through protease release by keratinocytes (23,24), complement activation (25), or combinations of these processes, merits further study. In any case, the autoantibodies from these patients can now be used to absolutely distinguish PV and PF at a molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Exactly how autoantibodies from these patients interact with these molecular complexes to cause loss of cell adhesion, whether directly by interfering with their function or indirectly through protease release by keratinocytes (23,24), complement activation (25), or combinations of these processes, merits further study. In any case, the autoantibodies from these patients can now be used to absolutely distinguish PV and PF at a molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro models using organ culture of skin have demonstrated that PV or PF IgG, in the absence of complement or inflammatory cells, can cause acantholysis (5)(6)(7). It is thought that the pemphigus IgG bound to the surface of the epidermal cell causes the release of one or more proteolytic enzymes, which results in acantholysis (7,(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Indirect immunofluorescence has been used to show that most patients with pemphigus also have circulating antibodies that bind to normal epidermis of most mammals and birds in the same intercellular pattern (2,3). Although light microscopic tissue immunofluorescence patterns appear to be intercellular, immunofluorescence performed on cell suspensions and immunoelectron microscopy have demonstrated that pemphigus antibodies bind to the keratinocyte cell surface (4)(5)(6)(7)(8) (9). The binding of pemphigus IgG to the keratinocyte cell surface probably results in the release of proteolytic enzymes that can cause acantholysis (6,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%